Al-Hiwalah dan Implementasinya pada Perbankan Syariah Di Titinjau dari Kaidah Fiqih - Hardiati, Neni; Januri, Januri (Ridwan Institute, 2021)
Hiwalah means a contract of help or tabarru, hiwalah is effectively applied to Islamic banking because there are rules contained therein, which provide benefits between the customer and the bank. This hiwalah activity requires fees from the first party to the second party the bank as a third party. Tabarru means giving sincerity from one individual to another without any imbalance affecting the ownership of the given person. Tabarru is carried out in providing assistance to individuals who are in conditions of economic difficulty, or to a social or religious institution that needs funds for the progress of society and religion. Therefore, tabarru 'is highly recommended in Islamic law. However, in a bank, there are services that are agreed upon as a risk from accounts payable, namely between the customer and the bank institution. Hiwalah activity itself means that activities on the responsibility of a muhil or in banking are called debtors to people who are obliged to pay debts that have such debts. Technically, Islamic banking is based on sharia principles in helping each other to ease the burden on parties who are having difficulty paying their debts, so as not to interfere with the financial cycle of economic activities in society. In transferring funds, this must be avoided from ribawi. In this article, we use literature study in al-hiwalah activities in Islamic banking according to fiqh principles.